Synthesis, characterization and ESR measurements of CoNiO nanoparticles - Köseoglu, Y; Yildiz, F; Salazar-Alvarez, G; Toprak, M; Muhammed, M; Aktas, B (Wiley-V C H Verlag Gmbh, 2005)
Powders of cobalt core with a nickel (11) oxide shell (CoNiO) have been studied by Electron Spin Resonance (ESR) technique in the temperature range of 10-300 K. A strong and broad (1300 G) single ESR peak in X-, K- and Q-band spectra has been observed at all the temperature ranges. While the resonance field remains almost constant, both the ESR line intensity and the line width were seen to increase first slowly down to T-c = 160 K. And then both the resonance field and the ESR signal intensity decrease and the line width increase with decreasing temperature. Below T. the intensity smoothly decrease down to 10 K. This kind of behavior is attributed to a typical spin-glass like behavior. Some small and relatively smooth changes at about 60 K, 90 K, 210 K, and 250 K are appeared as well. A linear dependence of resonance field to microwave frequency is observed at room temperatures and the effective g-value and internal field are theoretically found as 2,17 and 90 G, respectively. The experimental data indicate a very strong spin disorder (spin frustration) due to antiferromagnetic exchange interactions among the spins. This is attributed to the D-M anisotropy on the particle surfaces that it is expected to enhance due to increment of surface-to-volume ratio. (c) 2005 WILEYNCH Verlag GmbH & Co. KGaA, Weinheim.
Keywords: Ferromagnetic-Resonance; Magnetic-Properties; Size